2016
DOI: 10.1136/oemed-2015-103437
|View full text |Cite
|
Sign up to set email alerts
|

Mustard gas exposure and mortality among retired workers at a poisonous gas factory in Japan: a 57-year follow-up cohort study

Abstract: MG exposure significantly increases the long-term risk of death from respiratory cancer and chronic bronchitis/emphysema. The Okuno-jima MG Index may be a useful indicator for estimating cumulative MG exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 12 publications
0
17
1
Order By: Relevance
“…In addition, the eyes and the respiratory tract are other major targets of SM-induced toxicity (Kehe et al 2009). Long-term effects include impaired wound healing, chronic suppression of the immune system, and carcinogenesis, such as the development of lung cancers (Balali-Mood and Hefazi 2005;Doi et al 2011;Hosseini-khalili et al 2009;Mukaida et al 2017). Moreover, early on, it was recognized that SM suppresses hematopoiesis and causes bone marrow depletion and leukopenia (Balali-Mood and Hefazi 2005;Krumbhaar 1919;Pappenheimer and Vance 1920;Vedder 1925).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the eyes and the respiratory tract are other major targets of SM-induced toxicity (Kehe et al 2009). Long-term effects include impaired wound healing, chronic suppression of the immune system, and carcinogenesis, such as the development of lung cancers (Balali-Mood and Hefazi 2005;Doi et al 2011;Hosseini-khalili et al 2009;Mukaida et al 2017). Moreover, early on, it was recognized that SM suppresses hematopoiesis and causes bone marrow depletion and leukopenia (Balali-Mood and Hefazi 2005;Krumbhaar 1919;Pappenheimer and Vance 1920;Vedder 1925).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have consistently shown an increased risk of lung cancer among World War I veterans and workers from mustard gas production factories. The study by Mukaida et al 3 demonstrates excesses in cancer mortality from upper respiratory tract cancer, lung cancer, liver cancer and chronic bronchitis/emphysema, as well as cumulative dose-related increased mortality from respiratory cancer, lung cancer and chronic bronchitis/emphysema among former workers. Excesses in mortality from liver and stomach cancer were also observed, but the risks did not follow the cumulative estimates of mustard gas exposure.…”
mentioning
confidence: 99%
“…The long-term health consequences of such exposure include epithelial fibrosis and cancer and have been the subject of long-term follow-up studies, especially among military personnel and inhabitants of war-stricken areas in which chemical weapons were used 2. So, does the study by Mukaida et al 3 bring anything new to the existing knowledge on the consequences of long-term exposure to mustard gas? We are convinced that that answer is yes, and here we will dwell on the reasons why.…”
mentioning
confidence: 99%
See 2 more Smart Citations